DEVELOPMENT OF AN EVIDENCE-BASED REGULATORY GOVERNANCE FRAMEWORK FOR PUBLIC-PRIVATE PARTNERSHIPS PROJECTS IN MALAYSIA - UMAR, ABDULLAHI AHMED (2014)
Public-private partnerships (PPP) or private finance initiatives (PFI) is a procurement strategy that was though< would solve all the problems associated with the traditional procurement method. Its proponents had touted its ability to help manage the twin risks of time and cost overruns, deliver better quality services and offer better value for money more than other procurement types. Realizing that it is granting a 'legal' monopoly to private interests, governments worldwide created regulatory agencies to oversee these too-big-to-fail projects. Regulatory agencies were saddled with the tasks of ensuring the providers worked in accordance with the letter and spirit of the contracts while making a fair return on investments. After nearly two decades of the practice, consumers globally are increasingly becoming disenchanted with the service quality while the providers are reporting increased profitability. It was thought granting autonomy to these regulators would solve the problem.